Rainfed integrated farming systems for arid zone agriculture diversification for resilience - Tanwar, S. P. S.; Singh, Akath; Kumar, Parveen; Mathur, B. K.; Patidar, M. (Indian Farming, 2018)
This model provided fodder for 1.5-2 ACU/ha (1 ACU= 1 cattle or 6 small ruminants). Tharparkar cattle and Marwari breed of sheep and goat were reared. The proportion of land allocated to crop, trees and grasses was 50:20:30. This can be adjusted as per quality of land and requirement of the farmer. It took about 5 to 6 years for establishment and thereafter gave an annual income of more than ` 50, 000/ha. It also generated >130 mandays/ha-1 wages which were additional to the net returns.